Apert syndrome: Surgical outcomes and perspectives. Issue 9 (September 2016) - Breik, Omar; Mahindu, Antony; Moore, Mark H.; Molloy, Cindy J.; Santoreneos, Stephen; David, David J.
Abstract: Purpose: Apert syndrome is a rare congenital malformation with severe craniofacial anomalies. The aim of this study was to review the outcomes of craniofacial and neurosurgical interventions in Apert syndrome patients treated at a single institution. Materials and methods: A retrospective review of all patient records with a diagnosis of Apert syndrome assessed and managed in the Australian Craniofacial Unit (ACFU) from 1985 to 2013 was conducted. Results: A total of 94 patients were identified, and 130 transcranial procedures were performed. Of the patients, 83 underwent a fronto-orbital advancement (FOA) as their primary procedure, and 18 patients also underwent a posterior vault procedure. Twenty patients underwent a fronto-facial monobloc advancement. Overall, 70% of patients underwent at least 2 transcranial procedures. Shunts were inserted in 2 patients preoperatively and in 5 patients postoperatively for cerebrospinal fluid (CSF) leaks or acute hydrocephalus. Re-do FOAs were performed in 8 patients. Patients who underwent an FOA at the age of more than 18 months had no recurrence of raised intracranial pressure (ICP). Of 18 patients who also underwent a posterior vault procedure, 1 patient had recurrence of raised ICP. Midfacial surgery was performed early if there was evidence of obstructive sleep apnoea (OSA), but delayed midfacial surgery was preferred. Complications were reported in 18% of procedures. The most common complications were CSF leaks and acute hydrocephalus. Conclusion: Shunting is rarely required in Apert syndrome patients, confirming a predominantly nonprogressive ventriculomegaly. FOA appears to be a more stable procedure when performed at an age of more than 18 months. Undergoing a posterior vault procedure may reduce the risk of recurrent raised ICP and lead to fewer transcranial procedures needed in childhood. Midfacial surgery should be delayed until adolescence where there is no evidence of OSA, psychological disturbance, or complications of exorbitism. Complications are rare when these patients are treated by an experienced craniofacial team.